THE ROLE OF THE PRINCIPAL IN IMPROVING SCHOOL BRANDING SMP MUH 2 KARTASURA - Perdana, Niko; Azzani, Mohammad Zakki (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
In the field of education, school branding is a complex phenomenon that has many aspects. Therefore, the principal needs to have skills in improving school branding in order to be able to face increasingly tight competition. This study aims to describe the role of the principal and the supporting and inhibiting factors in improving the branding of SMP Muhammadiyah 2 Kartasura. The research method used is a descriptive qualitative approach including field research. The results of the study indicate that the role of the principal in improving school branding includes: The principal ensures that the school account is running well. The principal maintains communication with the school, parents of students, and alumni. The principal improves the quality of teachers. The principal improves facilities and infrastructure. Supporting factors in improving school branding include: Professional teachers. Positive school culture. The inhibiting factors include: Lack of funding and the presence of competitors in the school's environmental zone.